Overview of experiment design and comparison of models participating in phase 1 of the SPARC Quasi-Biennial Oscillation initiative (QBOi) - Butchart, N; Anstey, J; Hamilton, K; Osprey, S; McLandress, C; Bushell, A; Kawatani, Y; Kim, Y; Lott, F; Scinocca, J; Stockdale, T; Bellprat, O; et al. (European Geosciences Union, 2017)
The Stratosphere-troposphere Processes And their Role in Climate (SPARC) Quasi-Biennial Oscillation initiative (QBOi) aims to improve the fidelity of tropical stratospheric variability in general circulation and Earth system models by conducting coordinated numerical experiments and analysis. In the equatorial stratosphere, the QBO is the most conspicuous mode of variability. Five coordinated experiments have therefore been designed to (i) evaluate and compare the verisimilitudeof modelled QBOs under present-day conditions, (ii) identify robustness (or, alternatively the spread/uncertainty) in the simulated QBO response to commonly imposed changes in model climate forcings (e.g., a doubling of CO2 amounts) and, (iii) examine model dependence of QBO predictability. This paper documents these experiments and the recommended output diagnostics. The rationale behind the experimental design and choice of diagnostics is presented. To facilitate scientific interpretation of the results in other planned QBOi studies, consistent descriptions of the models performing each experiment set are given, with those aspects particularly relevant for simulating the QBO tabulated for easy comparison.